Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/w12123301
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Soil Erosion Resistance of Gully Head Along a 25-Year Revegetation Age on the Loess Plateau

Abstract: The effects of vegetation restoration on soil erosion resistance of gully head, along a revegetation age gradient, remain poorly understood. Hence, we collected undisturbed soil samples from a slope farmland and four grasslands with different revegetation ages (3, 10, 18, 25 years) along gully heads. Then, these samples were used to obtain soil detachment rate of gully heads by the hydraulic flume experiment under five unit width flow discharges (2–6 m3 h). The results revealed that soil properties were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
3
8
0
Order By: Relevance
“…Quantifying the impacts of slope length and grass cover on soil erosion showed that the impact of grass cover on soil loss was stronger than that of the slope length, which is similar to the results of Bircher et al [47]. The effects of the interference of the grass canopy and the change of root system on soil properties also hold positive significance for the control of soil erosion [48]. The above-ground part of vegetation has been harvested or removed; the root system of the vegetation still exerts a good control effect on soil erosion [49].…”
Section: Influence Of the Slope Length On The Effect Of Grass Cover O...supporting
confidence: 84%
“…Quantifying the impacts of slope length and grass cover on soil erosion showed that the impact of grass cover on soil loss was stronger than that of the slope length, which is similar to the results of Bircher et al [47]. The effects of the interference of the grass canopy and the change of root system on soil properties also hold positive significance for the control of soil erosion [48]. The above-ground part of vegetation has been harvested or removed; the root system of the vegetation still exerts a good control effect on soil erosion [49].…”
Section: Influence Of the Slope Length On The Effect Of Grass Cover O...supporting
confidence: 84%
“…The velocity showed multiple peak and valley trends over time. The soil on the bare tableland was easily eroded (Chen et al, 2020; Guo et al, 2018), and the soil surface was easily washed by runoff to reshape its topography (Samani et al, 2016; Wells et al, 2010). This process caused the topography of the tableland to be uneven.…”
Section: Discussionmentioning
confidence: 99%
“…Soil erosion occurred in areas where intense interactions among strata at the surface of land and environmental factors interact including water, wind, freeze-thaw, gravity, etc. [5][6][7]. Freeze-thaw erosion was the result of frequent changes in temperature, resulting in changes to soil and rock physico-chemical properties and occurs to a greater extent at high altitudes and latitudes in cold regions [8,9].…”
Section: Introductionmentioning
confidence: 99%